2015
DOI: 10.1021/acscatal.5b00094
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the N–Pd Interaction in Nitrogen-Doped Carbon Nanotube Catalysts

Abstract: In this work, the geometric and electronic structure of N species in N-doped carbon nanotubes (NCNTs) is derived by X-ray photoemission (XPS) and absorption spectroscopy (NEXAFS) of the N 1s core excitation. Substitutional N species in pyridine-like configuration and another form of N with higher thermal stability are found in NCNTs. The structural configuration of the high thermally stable N species, in the literature often referred to as graphitic N, is assessed in this work by a combined theoretical and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
326
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 380 publications
(362 citation statements)
references
References 81 publications
18
326
0
18
Order By: Relevance
“…Hence, the atoms seen by aberrationcorrected STEM are in the Pd 2+ state stabilized by nitrogen of the support. Very recently, Arrigo et al 27 observed similar changes in NEXAFS spectra of nitrogen after Pd deposition and assigned them to the formation of a covalent bond of Pd with pyridinic nitrogen with partial ionic character consistent with the shift of the binding energy of Pd 3d close to the Pd 2+ state.…”
Section: Ev We Have Assigned It To Nitrogen Species Interacting Withmentioning
confidence: 72%
See 4 more Smart Citations
“…Hence, the atoms seen by aberrationcorrected STEM are in the Pd 2+ state stabilized by nitrogen of the support. Very recently, Arrigo et al 27 observed similar changes in NEXAFS spectra of nitrogen after Pd deposition and assigned them to the formation of a covalent bond of Pd with pyridinic nitrogen with partial ionic character consistent with the shift of the binding energy of Pd 3d close to the Pd 2+ state.…”
Section: Ev We Have Assigned It To Nitrogen Species Interacting Withmentioning
confidence: 72%
“…The N 1s lines at ~398.1 (N1), ~399.8 (N2), ~400.7 (N3) and ~402.4 eV (N4) were attributed to pyridinic, pyrrolic, graphitic and oxidized nitrogen species, respectively. 25,27,34,35 The first three species are present in approximately the same concentrations (~30% , Table S2, Supporting information). For the samples with the reduced deposited Pd, a better fit of the N 1s spectra could be achieved accepting the presence of one more type of nitrogen species with a binding energy of 398.7-…”
Section: Pd Interaction With the Supportmentioning
confidence: 91%
See 3 more Smart Citations